ATRT-01. Reconstitution of cGAS/ STING pathway via epigenetic reprogramming leads to anti-viral inflammatory signaling in Atypical teratoid rhabdoid tumors (ATRTs). (3rd June 2022) - Mangoli, Avani; Hariharan, Seetha; Ashley, David; Fuller, Rebecca; Bowie, Michelle; Briley, Aaron; Brown, Michael; Hostettler, Janell
Abstract: BACKGROUND: Atypical teratoid rhabdoid tumors (ATRTs) are highly aggressive brain tumors that affect young children characterized by biallelic inactivation of the SMARCB1 gene. Though patients benefit from multimodal therapy, there is no improvement in overall survival which necessitates the exploration of alternative approaches. Innate-based immune and epigenetic therapies have shown benefits in several cancers. The role of innate immune signaling has not been investigated in ATRTs. Our previous data from several ATRT cell lines showed loss of expression of key innate signaling components, like cGAS and STING that are needed for sensing extracellular dsDNA. Additionally, ATRT cell lines do not respond to STING agonists, like cGAMP or ISD. RESULTS: Co-treatment of ATRT cell lines, BT-12 and BT-16 with two epigenetic modulators, panobinostat and decitabine, leads to re-expression of cGAS and STING in a time-dependent manner. Furthermore, treatment with decitabine alone leads to demethylation of several CpG sites on the STING promoter and increased expression of STING mRNA. Panobinostat and decitabine co-treatment reconstitute STING-mediated innate signaling, as measured by IRF-3 and STAT1 phosphorylation and production of ISG-15 and IFIT-1 after treatment with cGAMP, a STING agonist. Co-treatment with panobinostat and decitabine also induced expression of antiviral pro-inflammatory chemokines/cytokines in ATRT cell lines, including type III IFN, IL-6, IL-8, IL-28, and IL-29. CONCLUSION: Our data suggest that ATRT cell lines are unresponsive to innate agonists possibly due to the loss of expression of key innate immune components. However, the cGAS/STING pathway is reactivated by epigenetic drugs, specifically the combination of panobinostat and decitabine. This is further potentiated by treating with STING agonists like cGAMP. Combination treatment of ATRT cell lines with panobinostat and decitabine also induced antiviral inflammatory signaling. This response could be a potential treatment modality to inhibit tumor growth and/or mediate cancer immunotherapy in these aggressive tumors.